Transformational leadership - Srivastava, Mrityunjay Kumar (New Delhi : Macmillan India, 2003)
With reference to individual business leaders from various businesses in India.
Originally presented as author's thesis.
Keywords: Leadership; Organizational change; Executive ability; Businessmen